Pharmacokinetic profile of promising acetylcholinesterase reactivators K027 and K203 in experimental pigs. (5th May 2017) - Karasova, Jana Zdarova; Kvetina, Jaroslav; Tacheci, Ilja; Radochova, Vera; Musilek, Kamil; Kuca, Kamil; Bures, Jan
Highlights: The pharmacokinetic profiles of two promising oximes (K027and K203) were assessed. The non-rodent animal model was used (experimental pigs). Results should closely demonstrate real pharmacokinetic profiles in case of emergency. The pigs plasmatic profiles may help us to better understand inter-species differences. The human pharmacokinetic profiles may be better estimated. Abstract: Standard treatment of organophosphorus compounds (OPs) poisoning includes administration of an anti-muscarinic (atropine), anticonvulsive (diazepam) and acetylcholinesterase reactivator (oxime). From a wide group of newly synthesized oximes, oxime K027 and oxime K203 seem to be perspective compounds in some specific OPs intoxication. The available in vitro and in vivo preclinical data indicate that both oximes may be considered for potential human use. The main aim of this study was to establish plasmatic concentration curves of both oximes after intramuscular (i.m.) and intragastric (i.g.) application with subsequent pharmacokinetic analysis and study distribution after (i.m.) application on a non-rodent animal model (experimental pigs; 1500 mg/animal). According to the results, both oximes had similar C max (K027: 106 ± 19 μg/mL and K203: 111 ± 8 μg/mL) in T max 19 ± 5 min, respectively, in 22 ± 3 min. Bioavailability of oxime K027 calculated as AUCtotal (8389 ± 1024 min μg/mL) was halved compared to oxime K203 (16938 ± 795 min μg/mL). The highest concentration from peripheral tissues was found in the kidney and lung, but the brain concentrations stay very low, the plasma/brain ratio being approximately 1%. The applied doses were derived from the recommendation where it is possible to use three autoinjectors to save human life. The results provide us with knowledge about the pharmacokinetics and distribution of these new oximes and may help us to better estimate the human pharmacokinetic profile.